Kesantunan Berbahasa Siswa Sebagai Upaya Mengatasi Perilaku Bullying Pada Siswa Sekolah Dasar - Nurhidayat, M. Arif; Mafruhan, Mafruhan; Fahmudita, Afika; Susandi, Ari (Jurnal Pendidikan Dasar, 2024)
Education is an effort to prepare students' mindset and strengthen their character. In education, students are shaped to have a polite character. However, technological developments make students' characters experience changes, especially in students' language impressions, language politeness is an important thing to use in interacting with other individuals. If the language used to communicate tends to be impolite, it will have a negative impact, especially bullying behavior on students. Therefore, the use of polite language can prevent bullying which will cause harm to students.